Design Contextual Problems and Solutions Related to Linear Programming Topics with The Help Of Geogebra - Harini, Novita Vindri (Noumerico: Journal of Technology in Mathematics Education, 2024)
This preliminary research will be conducted at the beginning of the operations research course. Operations research is an extension of the topic of linear programming mathematics that is taught in high school. This research aims to describe the results of the work of operations research class students regarding how to design contextual problems and solve them using GeoGebra’s help. This research uses a qualitative approach, namely through in-depth observation of the results of student work on worksheets. After data analysis, it was found that in designing problems, students could produce realistic contextual problems using two variables and a single optimum solution type. Interestingly, they use contexts that are very close to current world trends, for example, Korean boy bands, culinary delights, types of flower arrangements, and so on. Meanwhile, in the solution process, using GeoGebra has proven to facilitate problem-solving by implementing the strategy and checking the results. They use the probe concept to find the optimum solution, and GeoGebra dramatically speeds up the process